Localized mirror-like surface electropolishing and void-free submillimeter-scale electrodeposition for fabrication of watch parts with complex geometries - Lim, Chee Siong (Nanyang Technological University, 2022)
This project is a collaboration project between Nanyang Technological University and Seiko Manufacturing (Singapore) Pte. Ltd., a subsidiary of leading wristwatch manufacturer Seiko Watch Corporation. This project focuses on the research and development of localized electropolishing technique as an alternative polishing method to mechanical polishing in conventional watch fabrication, which is very labor-intensive, highly skill-dependent and costly. Complex features of miniature watch part of which dimensional accuracy should be kept were masked by non-conductive photoresist through a simplified photolithography process. Anodic dissolution behavior of leaded brass material in Glycerol-added phosphoric acid solution was investigated. Technical issues like adverse effect of viscous layer, removal of macroscopic defect and formation of lead particles were discussed with proposed solutions. Experiment results showed that a near mirror surface finishing could be obtained by conducting localized electropolishing on photoresist-masked watch part, suggesting a high potential of substituting mechanical polishing with electropolishing which is less dependent on human skill therefore better quality consistency and lower production cost. Process scale-up and other potential application to which the developed localized electropolishing technique could be implemented, were also discussed in this thesis. Feasibility of fabrication of void-free submillimeter scale nickel component by single additive bottom-up electrodeposition was demonstrated as well.